A nontargeted and targeted metabolomics study on the dynamic changes in metabolite levels during the anaerobic treatment of γ-aminobutyric acid (GABA) tea. (May 2020) - Dai, Weidong; Xie, Dongchao; Lin, Zhiyuan; Yang, Chen; Peng, Qunhua; Tan, Junfeng; Lin, Zhi
Abstract: γ-Aminobutyric acid (GABA) tea is a popular tea with high GABA content (>1.5 mg/g). In this study, the influence of anaerobic treatment, which is a key manufacturing process for GABA tea, was investigated by a nontargeted metabolomics method combining with targeted compounds quantifications. The results showed that the anaerobic treatment not only led to a ~16-fold increase in GABA content but also caused significant changes in the levels of TCA cycle metabolites, dimeric flavanols, lipids, bases/nucleosides, and most of amino acids ( p  < 0.05). The levels of alkaloids, flavanols, and flavonol/flavone glycosides were slightly fluctuated. After the removal of anoxic conditions, the GABA content remained stable, while dimeric flavanols, flavanols, aroma glycosides, and most of amino acids varied. This study provides a comprehensive characterization of GABA tea processing in a view of dynamic metabolome and offers a theoretical basis for quality control of GABA tea processing. Highlights: Metabolomics method and targeted quantifications for the study of GABA tea. A dynamic view on metabolites during and after anaerobic treatment. The anaerobic treatment led to a ~16-fold increase in GABA content. Anaerobic treatment resulted in complex changes in multiple metabolic pathways.